Surgical and endoscopic interventions that reduce lung volume for emphysema: a systemic review and meta-analysis - Geffen, Wouter H. van; Herth, Felix (The lancet. Respiratory medicine, 2019)
Summary - Background - Severe emphysema is a debilitating condition with few treatment options. Lung volume reduction procedures in the treatment of severe emphysema have shown excellent results in selected patients but their exact role remains unclear with studies reporting a wide variation in outcomes. We therefore aimed to evaluate the effects of volume reduction. - Methods - We did a systematic review and meta-analysis. We searched MEDLINE on Sept 29, 2016, for trials of lung volume reduction in patients with emphysema, and we did an updated search on Embase and PubMed on June 18, 2018. We only included randomised controlled studies published in English evaluating the intervention with either sham or standard of care. Inclusion was limited to trials of techniques in which there was sustainable volume reduction. Primary outcomes were residual volume, FEV1, St George's Respiratory Questionnaire (SGRQ), and 6-min walk distance (6MWT). Secondary outcomes were severe adverse events (including mortality), short-term mortality, and overall mortality. We extracted summary level data from the trial publications and where necessary we obtained unpublished data. A random-effects model with the I2 statistic was used to determine heterogeneity and trial weight in each analysis. The study is registered with the PROSPERO database, number CRD42016045705. - Findings - We identified 4747 references in the search, and included 20 randomised controlled trials of lung volume reduction involving 2794 participants with emphysema. Following lung volume reduction from any of the interventions in pooled analyses (ie, surgery, endobronchial valve, endobronchial coil, or sclerosing agents), the mean differences compared with the control were reduction in residual volume of 0·58 L (95% CI −0·80 to −0·37), increase in FEV1 of 15·87% (95% CI 12·27 to 19·47), improvement in 6MWT of 43·28 m (31·36 to 55·21), and reduction in the SGRQ of 9·39 points (−10·92 to −7·86). The odds ratio for a severe adverse event, which included mortality, was 6·21 (95% CI 4·02 to 9·58) following intervention. Regression analysis showed improvements relative to the degree of volume reduction: FEV1 (r2=0·86; p<0·0001), 6MWT (r2=0·77; p<0·0001), and SGRQ (r2=0·70; p<0·0001). Most studies were at high risk of bias for lack of blinding, and heterogeneity was high for some outcomes when pooled across all interventions, but was generally lower in the subgroups by intervention type. - Interpretation - Despite limitations of high risk of bias and heterogeneity for some analyses, our results provide support that lung volume reduction in patients with severe emphysema on maximal medical treatment has clinically meaningful benefits. These benefits should be considered alongside potential adverse events. - Funding - None.
Available online 8 February 2019
Gesehen am 02.05.2019